(untitled) (Research, Society and Development, 2022)
Pain is a highly subjective and multifactorial experience. Most patients undergoing surgical procedures experience postoperative pain. Thus, the aim of this study was to review the available management for the treatment of postoperative pain in literature. The research consists of an integrative literature review, carried out in the PubMed database, which considered articles published in Portuguese or English, between January 2015 and November 2021. Postoperative pain management is still unsatisfactory. Oral analgesia is the mainstay of pain control. Preoperative, intraoperative, and postoperative pain is usually treated with a combination of oral medications, including acetaminophen or nonsteroidal anti-inflammatory drugs and oral opioid analgesics. Opioids have many side effects, including tolerance and addiction. The multimodal approach to postoperative pain is the most recommended. Non-pharmacological pain control measures have been shown to be effective and should be encouraged.